Pengaruh Kepemimpinan Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Rumah Sakit Muhammadiyah Palembang - Marlina, Leni; Moelyati, Trisniarty Adjeng; Yamaly, Fadhil (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
This research aims to determine the influence of Leadership, Work Motivation, and Work Discipline on the Performance of Employees at the Palembang Muhammadiyah Hospital. The sampling technique in this research uses the Cluster Sampling technique by taking samples from 217 employees of the Palembang Muhammadiyah Hospital. The research method used is associative research using primary data obtained from the results of questionnaire answers. This research shows that simultaneously and partially, there is a positive and significant influence of Leadership, Work Motivation, and Work Discipline on the Performance of Employees at the Palembang Muhammadiyah Hospital. The three variables, leadership, work motivation, and work discipline, were able to contribute to explaining changes that occurred in employee performance by 83.3%, providing practical implications for hospital administrators and professionals in the field of human resources